Three cases of antibody-LGI1 limbic encephalitis and review of literature. (3rd July 2019) - Bing-Lei, Wang; Jia-Hua, Zheng; Yan, Li; Zan, Yue; Xin, Bian; Jian-Hua, Shen; Hui-Juan, Wang
Abstract: Purpose: Antibody-LGI1 limbic encephalitis (LGI1-Ab LE) is an anti-neuronal surface antigen-related autoimmune encephalitis. we report three cases of LGI1-Ab LE, describe the characteristics of clinical manifestation, course of evolution, imaging manifestation and treatment outcomes. Methods: Data from patients diagnosed with LGI1-Ab LE in the Second Hospital, Hebei Medical University, from June 2016 to July 2017, were retrospectively collected and analyzed. We followed up the patients for 90 days. Results: Two of the three patients were females, the average age of onset is 53 years old. Epilepsy is the most common clinical manifestations, and one of patients developed faciobrachial dystonic seizures (FBDS), which was recently described as a characteristic feature of LGI1-Ab LE. All patients had cognitive impairment in different degrees and abnormal signal of hippocampus in cranial MRI. All serum LGI1 antibodies were positive, whereas one LGI1 antibodies of CSF were negative. All patients accepted first-line immune therapy and had a good outcome. Conclusion: LGI1-Ab LE, which is an autoimmune disease, is rare clinically and mostly nonparaneoplastic. We suggest that LGI1-Ab LE be considered in any patient with acute or subacute onset, cognitive dysfunction, various types of seizures, accompanied by mental disorders and hyponatremia, MR showed the involvement of the limbic system. It is necessary to have LE-related antibodies tested. Early immunotherapy can significantly improve the patient's overall prognosis. At the same time, we should also pay attention to the possibility of potential tumors.